2020
DOI: 10.1177/0020764020966009
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-peer contact, social support and self-stigma among people with severe mental illness in Hong Kong

Abstract: Background: Self-stigma exerts a range of adversities for persons with severe mental illness (SMI), however, little is known about the association between peer contact, social support and self-stigma. Aims: This study aimed to explore the mediating role of social support on the relationship between peer contact and self-stigma among persons with SMI in Hong Kong. Methods: A total of 159 persons with SMI (schizophrenia and mood disorder) in community service centres participated in the study through completing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 76 publications
5
19
0
Order By: Relevance
“…The focus of contact program, thus, could not only be on increasing the frequency of contact in different social systems and strengthening the favorable aspect of contact, but also consider local context to tailor the intervention. The results of this study also support that the enhancing contact model (ECM) on increasing the amount and positive level of contact should be crucial to reduce prejudice and social distance (Li et al, 2020). In addition, as our findings show, behavioral change toward more social acceptance and less discrimination is not affected by the extent of mental health knowledge.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The focus of contact program, thus, could not only be on increasing the frequency of contact in different social systems and strengthening the favorable aspect of contact, but also consider local context to tailor the intervention. The results of this study also support that the enhancing contact model (ECM) on increasing the amount and positive level of contact should be crucial to reduce prejudice and social distance (Li et al, 2020). In addition, as our findings show, behavioral change toward more social acceptance and less discrimination is not affected by the extent of mental health knowledge.…”
Section: Discussionsupporting
confidence: 79%
“…Given the deleterious barriers that stigma poses on the recovery of PMI, a considerable body of research has found contact-based anti-stigma interventions to be a more effective strategy compared to protest and education (Evans-Lacko et al, 2012; Griffiths et al, 2014; Li et al, 2020; Mehta et al, 2015; Thornicroft et al, 2016). Allport (1954) formulated intergroup contact theory postulating that prejudice could be reduced when cross-group contact occurs within four conditions, including equal status, common goals, cooperation, and authority support.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-stigma campaigns need to balance wide and broad approaches that seek to challenge discrimination in a large population of people with more local campaigns which focus on challenging the opinions of small groups[ 26 ]. This finding is reinforced by another study[ 27 ] which suggests that such strategies could be developed to also reduce self-stigma in people experiencing mental health issues. However, little is known about what elements of contact are effective in challenging stigma[ 10 ]; for example, is it equal status or promoting understanding about experiences of mental ill-health that makes contact-based strategies effective?…”
Section: Effective Methods To Promote Anti-stigma Workmentioning
confidence: 84%